(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2026)
Speaking anxiety is widely recognized as one of the most serious psychological barriers affecting foreign language learners, particularly in English for Specific Purposes (ESP) classrooms where communication skills are directly connected to academic and professional development. Among philology undergraduates, teacher evaluative discourse plays a critical role in shaping students’ emotional experiences, communicative confidence, and classroom participation. The present study investigates the impact of teacher feedback styles on speaking anxiety and explores how evaluative discourse may either reduce or intensify professional face-threat among ESP learners.